Implementation of 'Usyur in Tax Revenue During the Covid-19 Period in Medan City - Nurlaily Nurlaily; Muhammad Yafiz; Yenni Samri Juliati Nasution (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2022)
The coronavirus has had a tremendous impact on the world economy, many people's businesses have experienced a decline in revenue during covid-19. Hotel and restaurant tax revenues during the covid19 period have also been paralyzed. So that tax deposits become the heaviest burden for business actors. In this case, how does the concept of 'Usyur see the problems that plague this world so that tax revenues during the Covid-19 pandemic. This research uses qualitative research methods with descriptive analysis. A qualitative approach is an approach that seeks to interpret the meaning of an event as an interaction of human behavior in a particular situation. The results found are that 'Usyur provides relief to business actors when an outbreak hits the world, but in its implementation it often experiences obstacles and obstacles and its application has not been implemented in Indonesia. 'usyur has not been fully implemented even though there are sharia hotels and restaurants, 'usyur has not been as busy as it is going well, although the concept will lead to the concept of sharia tax revenue. This is an input for future business actors in realizing sharia tourism and hotels